Studi Komparatif Implementasi Program Sekolah Penggerak SMAN 1 Muara Beliti Dan SMAN Sumberharta Di Kabupaten Musi Rawas - Wahyu Sutopo, Timbul; Putri Kartiwi, Asti (UNIVERSITAS BENGKULU, 2024)
The purpose of this study compares the implementation of the Mobilizing School Program at SMAN 1 Muara Beliti and SMAN Sumber Harta in Musi Rawas District, focusing on five aspects: school leadership, teacher pedagogical competencies, student character, learning environment, and supporting and hindering factors of the program. The research employs a comparative study method with a qualitative approach, collecting data through interviews, observations, and documentation. The results indicate that both schools implement student-centered leadership and are actively engaged in professional development but with different approaches. The principal of SMAN 1 Muara Beliti emphasizes monitoring teaching quality, while the principal of SMAN Sumber Harta focuses more on teacher mentoring. In terms of pedagogical competencies, teachers at both schools apply differentiated learning, with SMAN 1 Muara Beliti utilizing more learning strategies and technologies, whereas SMAN Sumber Harta prioritizes a personal approach. Student character highlights religious and national values, with varying program emphases. The learning environment in both schools demonstrates high enthusiasm despite socio-economic challenges, supported by parents and stakeholders. Overall, the implementation of the Mobilizing School Program in both schools positively impacts the improvement of educational quality, although challenges regarding budget and resources persist.